2000
DOI: 10.1377/hlthaff.19.4.36
|View full text |Cite
|
Sign up to set email alerts
|

Managing Medicaid Managed Care: Are States Becoming Prudent Purchasers?

Abstract: PROLOGUE: After turning to managed care to hold down costs, states found that they needed to shed their regulatory mentality toward Medicaid services and learn to implement policy through the contracting process. Theoretically, contracting relieves both states and service providers of a trying, micromanagerial relationship and creates a conceptually satisfying single point of accountability.In practice, states must build new capabilities to monitor and assess health plan performance. Their new role as hard-nos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Most of the articles classified as multiple case studies did not describe a systematic strategy for comparing cases (e.g., replication logic, qualitative comparative analysis). Some authors made comparative statements in the results section with no mention of a systematic analysis strategy (L. D. Brown & Kraft, 2008; Fossett et al, 2000; Luck & Peabody, 2000; McHugh, Staiti, & Felland, 2004). Other authors did not make any “cross-case” comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the articles classified as multiple case studies did not describe a systematic strategy for comparing cases (e.g., replication logic, qualitative comparative analysis). Some authors made comparative statements in the results section with no mention of a systematic analysis strategy (L. D. Brown & Kraft, 2008; Fossett et al, 2000; Luck & Peabody, 2000; McHugh, Staiti, & Felland, 2004). Other authors did not make any “cross-case” comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies of state contracting for social services have suggested that states find it difficult to hold contractors accountable for their performance (Fossett et al 2000; Romzek and Johnston 2002). This study attempts to explain this dynamic by focusing on the structures of social service contracts, the demands of contract management, and a number of related questions.…”
Section: Contracting For Social Servicesmentioning
confidence: 97%
“…16,18 Some of the foremost architects of managed care nationally have noted that approximately one third of the US population lives outside of metropolitan areas with populations large enough to support 3 or more managed care organizations in competition. [2][3][4][5] Thus far, the impact of Medicaid managed care on access to care for low-income persons remains unclear. 19 Barriers that states encounter with Medicaid managed care in rural areas include an insufficient number of covered lives to make prepayment feasible, limited prior penetration by managed care organizations, limited willingness of managed care organizations to participate in rural areas, and few primary care or specialty providers; such issues have led to the initiation of primary care case management in some rural areas.…”
mentioning
confidence: 99%